STRATEGI MANAJEMEN KOMUNIKASI DALAM PENANGGULANGAN KEMACETAN LALU LINTAS DI KAWASAN PERKOTAAN - Silfiana Dian Lestari; Fitri Susiswani Isbandi; Rini D. Fauzi; Katry Anggraini; Amanda, Amanda; Ade Siti Khaeriah (Journal of Innovation Research and Knowledge, 2025)
Traffic congestion in urban areas is a complex issue that requires an effective communication approach for its mitigation. This study aims to analyze communication management strategies in addressing traffic congestion in urban areas and to identify the roles of various stakeholders in the traffic policy communication process. Using a qualitative approach and literature review method, this research examines various sources of literature that cover communication management theories, transportation policies, as well as the roles of government, society, and the private sector in tackling congestion. The findings of the study indicate that communication strategies based on collaboration, transparency, and the use of information technology are key factors in the successful management of traffic congestion. Furthermore, the involvement of various parties, including the government, society, and the private sector, in the traffic policy communication process significantly impacts the implementation of these policies. This research provides valuable insights for policymakers in designing more effective communication strategies to reduce traffic congestion in urban areas